Single Mother, Migrant Domestic Workers: Exploring the coping experience of low-income Zimbabwean women raising their children in South Africa - Johnson, Madeline Jane (Department of Sociology, 2023)
Zimbabweans are the largest migrant group in South Africa, and many of them are women who end up working informally as domestic workers (DWs). This study investigated the way that Zimbabwean single mother migrant domestic workers (MDWs) experience and cope with the burden of care. Specifically, it looks at women who have decided at some point in their migrancy experience to bring their children to raise in South Africa. The purpose of this research was to understand how they are managing to care for their children given their circumstances, and why they have chosen to do so as a family unit in South Africa rather than mothering from a distance - the norm as shown in international and Southern African migration literature on DWs. Due to financial troubles and social isolation associated with migrancy, single motherhood, and domestic work, their ability to cope with the burden of care is limited. This study is rooted in the theory that mothering in not a universal path, and that every woman will approach it differently based on her own familial, financial, cultural, racial, and personal circumstances that determine how she is able to practice mothering. This was a qualitative study and data was gathered via semi-structured, in depth interviews from a purposively-snowballed population sample of 13 women. This study found that the support networks of Zimbabwean single mother MDWs are actually quite limited, contrary to the existing literature base which highlights social support in migrant coping experiences. The social support that they receive - such as emotional support and/or informally compensated reciprocal child-watching arrangements - relieves some burden, but is insufficient, thus their childcare options are insufficient. Their coping mechanisms are primarily emotion focused, individual activities to tolerate their hardships, such as crying or listening to gospel music, because there are no practical solutions at this time. Choosing to bring their children to South Africa is a coping mechanism in itself which aims to reduce expenses associated with remittance and to alleviate the pain of family separation. Their deviation from the traditional Southern-African migrant norm of mothering from a distance indicates the possibility of evolving notions of motherhood and family in migrant and single parent contexts, as women follow their own individual paths in facing their unique circumstances of the burden of care. The findings of this study have serious implications for family and child welfare. Understanding single mother migration patterns is very important, and research in this area, like this study, may someday be able to inform policy, guide NGOs, and help to generate solutions for women facing a disproportionate burden of care.